The Revolutionary 'I' - Nichols, A. author. aut Link
XX, 187 p.
Keywords: In the winter of 1798-99, shut up in the freezing German town of Goslar, William Wordsworth began producing a series of lyrical fragments that appeared first in letters written to Coleridge and emerged eventually as source texts for The Prelude . These lyrics are revolutionary because they construct a new version of the autobiographical 'I'. The Revolutionary 'I' explores the numerous voices of the poetic speaker 'Wordsworth' and their relationship to the historical figure who shared the same name.